Mastering QuickBooks 2020 : the ultimate guide to bookkeeping and QuickBooks online - Shelton, Crystalynn (Packt Publishing, 2019)
QuickBooks is a bookkeeping software for finance professionals to manage business accounting demands and reports. This book will help you build the perfect budget, simplify tax return preparation, manage inventory, track job costs, generate income statements and financial reports, and every other accounting-related task crossing your desk at work.